Randomized controlled phase I/II study to investigate immune stimulatory effects by low dose radiotherapy in primarily operable pancreatic cancer - Timke, Carmen; Schmitz-Winnenthal, Friedrich Hubertus; Klug, Felix; Röder, Falk; Bonertz, Andreas; Reißfelder, Christoph; Rochet, Nathalie; Koch, Moritz; Tjaden, Christin; Büchler, Markus W.; Debus, Jürgen; Werner, Jens; et al. (BMC cancer, 2011)
The efficiencies of T cell based immunotherapies are affected by insufficient migration and activation of tumor specific effector T cells in the tumor. Accumulating evidence exists on the ability of ionizing radiation to modify the tumor microenvironment and generate inflammation. The aim of this phase I/II clinical trial is to evaluate whether low dose single fraction radiotherapy can improve T cell associated antitumor immune response in patients with pancreatic cancer.
Gesehen am 03.11.2022